Metformin and Thymoquinone Synergistically Inhibit Proliferation of Imatinib-Resistant Human Leukemic Cells - Glamoclija, Una; Mahmutovic, Lejla; Bilajac, Esma; Soljic, Violeta; Vukojevic, Katarina; Suljagic, Mirza (Frontiers in Pharmacology, 2022)
Chemotherapy resistance is one of the major challenges in cancer treatment, including leukemia. A massive array of research is evaluating combinations of drugs directed against different intracellular signaling molecules to overcome cancer resistance, increase therapy effectiveness and decrease adverse effects. Combining chemicals with proven safety profiles, such as drugs already used in therapy and active substances isolated from natural sources, could potentially have superior effects compared to monotherapies. In this study, we evaluated the effects of metformin and thymoquinone (TQ) as monotherapy and combinatorial treatments in chronic myeloid leukemia (CML) cell lines sensitive and resistant to imatinib therapy. The effects were also evaluated in primary monocytic acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) cells. Both compounds induced dose and time-dependent decrease of viability and proliferation in tested cells. Metformin had similar IC50 values in imatinib-sensitive and imatinib-resistant cell line. IC50 values of TQ were significantly higher in imatinib-resistant cells, but with a limited resistance index (2,4). Synergistic effects of combinatorial treatments were observed in all tested cell lines, as well as in primary cells. The strongest synergistic effects were observed in the inhibition of imatinib-resistant cell line proliferation. Metformin and TQ inhibited nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling and induced apoptosis in tested cell lines and primary cells. Enhanced effects of combinatorial treatment on induction of apoptosis were more dominant in imatinib-resistant compared to imatinib-sensitive CML cells. Primary cells were more sensitive to combinatorial treatments compared to cell lines. Combination of 1,25 mM metformin and 0,625 µM TQ increased levels of cleaved poly (ADP-ribose) polymerase (PARP), decreased levels of proliferation regulatory proteins and inhibited protein kinase B (Akt) and NF-κB signaling in primary CLL cell. This study demonstrates that combinatorial treatment of imatinib-resistant malignant clones with metformin and TQ by complementary intracellular multitargeting represents a promising approach in future studies.